2009
DOI: 10.1021/jp9058005
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of Gaseous Ammonium Nitrate at Low Pressure: Kinetic Modeling of Product Formation and Heterogeneous Decomposition of Nitric Acid

Abstract: The thermal decomposition of ammonium nitrate, NH(4)NO(3) (AN), in the gas phase has been studied at 423-56 K by pyrolysis/mass spectrometry under low-pressure conditions using a Saalfeld reactor coated with boric acid. The sublimation of NH(4)NO(3) at 423 K was proposed to produce equal amounts of NH(3) and HNO(3), followed by the decomposition reaction of HNO(3), HNO(3) + M --> OH + NO(2) + M (where M = third-body and reactor surface). The absolute yields of N(2), N(2)O, H(2)O, and NH(3), which can be unambi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…Park and Lin modeled the decomposition of AN at very low pressures (5‐6.2 Torr) using 115 reactions. The authors also conducted decomposition study experiments by pyrolysis/MS in a Saalfeld reactor.…”
Section: Decomposition Mechanisms Of Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Park and Lin modeled the decomposition of AN at very low pressures (5‐6.2 Torr) using 115 reactions. The authors also conducted decomposition study experiments by pyrolysis/MS in a Saalfeld reactor.…”
Section: Decomposition Mechanisms Of Anmentioning
confidence: 99%
“…Xu et al studied the reaction of AN with coal. They concluded that while the inorganic portion is nearly nonreactive with AN, the organic portion reacts readily.…”
Section: Reactions Involving Additional Substancesmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] Yet, few studies have been done on the catalytic decomposition of AN. [20,21] Also, these studies were generally performed under static conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Park and Lin and Skarlis et al have also proposed a decomposition path via NH 3 OH + as summarized in the following series of reactions:truerightNH4NO3NH4++NO3truerightNH4++NO3NH3OH++NO2truerightNH3OH++NO22HNO+H2normalON2normalO+2normalH2normalOtruerightNH3OH++NO2leftH2N2O2+H2normalOleftN2normalO+2H2normalO…”
Section: Introductionmentioning
confidence: 99%
“…In some energetic materials, the condensed phase reaction has the greatest effect on the combustion characteristics, and AN is included among these . Various reliable models of gas‐phase reactions have been proposed to date, all of which work to explain observed combustion behaviors . More recently, models for the liquid‐phase reactions of energetic salts have also been developed .…”
Section: Introductionmentioning
confidence: 99%